American entrepreneur 1990-2010: Black business ownership as a path way out of poverty and violence - Parker, Karen F. (Race and social problems, 2025)
Entrepreneurship is touted as a pathway to achieve economic mobility and this is particularly true among immigrants and Black Americans. There is little research on whether the rise in Black entrepreneuership is linked to the declining rates of violernce in urban areas, net of effects associated with the concentration of disadvantage. After generating two distinct measures of Black entrepreneurship using national-level business ownership data, we test to see if Black-owned businesses were significantly related to the documented decline in juvenile violence in larger US cities from 1990 to 2010. Our findings show an inverse relationship between Black entrepreneurship and youth violence across multiple cities in 1990 and 2000, while the rate of paid employees in Black firms contributed to a reduction of Black youth violence in 2010. Furthermore, our fixed-effect design confirms the growing presence of Black businesses is a significant contributor to the reduction in Black urban violence. In changing economic times, we discuss the theoretical and empirical importance of Black entrepreneurship as a way out of poverty and crime in urban areas.